Analisis Health Belief Model Perilaku Pencegahan Covid-19 pada Mahasiswa Kesehatan - Yohana Hepilita; Heribertus Handi; Fransiska Yuni Demang; Lusia Henny Mariati (Poltekkes Kemenkes Maluku, 2021)
Students are considered to have an important role in providing health information and education to the public by compiling appropriate narratives and informative content related to the management of Covid-19 and handling hoax busters. The concept of health belief model is a health belief model with 4 (four) main concepts, namely perceived susceptibility, perceived seriousness, perceived benefits, and perceived barriers. This study aims to describe and analyze the relationship of four (4) health belief model components with the prevention behavior of Covid-19 in health students. This research method uses a descriptive-analytic design with a correlation study approach. The sample used in this study amounted to 97 students with a sampling technique that is probability sampling cluster sampling. The results of the health belief model components that have a relationship with Covid-19 prevention behavior in respondents are the perceived susceptibility component with p-value=0.000 (p<0.05), the perceived severity component with p-value=0.000 (p<0.05), and the perceived benefit component. with p-value=0.0002 (p<0.05). The component that has no relationship with the respondent's Covid-19 prevention behavior is the perceived barriers component with a p-value=0.28 (p>0.05).